Comparison of Iliac Bone Transplantation with Bone Transport in the Treatment of Femur Fracture and Bone Defect. (3rd October 2022) - Huang, Wei; Zhu, Wenfeng; Lu, Wei
Abstract : Objective . To compare the curative effect of iliac bone transplantation with the bone transport in the treatment of femur fracture complicated with a bone defect. Methods . Patients with femur fractures and defects who were admitted to our hospital from January 1, 2020, to January 31, 2022, and met the inclusion criteria were retrospectively selected and allocated into an iliac bone transplantation group or a bone transport group. The treatment effect and quality of life of the two groups were compared. Results . A total of 98 patients who met the inclusion standards were enrolled, including 50 cases in the iliac bone transplantation group and 48 cases in the bone transport group. There were no significant differences in IL-6, IL-8, TNF- α, visual analog scale (VAS) score, or Japanese Orthopedic Association (JOA) score between the two groups on postsurgical day 1 (p = 0.051, 0.150, 0.102, 0.564, and 0.826 respectively), but there were significant differences in the above index on postsurgical day 7 (all p < 0.01 ). There were no significant differences in social function, physical function, role function, and cognitive function between the two groups one week after the operation (p = 0.245, 0.051, 0.102, and 0.067, respectively), but there were significant differences in the above parameters at one month after operation (p = 0.001, 0.005, 0.005, and 0.001, respectively). The total effective rate of the bone transplantation group was significantly better than that of the iliac bone transplantation group (p = 0.026 ). The number of postoperative complications in the bone removal group was significantly fewer than that of the iliac bone graft group (p = 0.001 ). Conclusion . Bone transport is effective in treating femur fractures complicated with bone defects, with fewer postoperative complications.